Community pharmacists' views on providing a reproductive health service to women receiving opioid substitution treatment: A qualitative study using the TDF and COM-B - Alhusein, N.; Scott, J.; Neale, J.; Chater, A.; Family, H. (Exploratory research in clinical and social pharmacy, 2021)
The absence of menstruation is common in women who use drugs. This can give a belief that conception is unlikely. When stabilised on Opioid Substitution Treatment (OST), fertility often returns, initially without realisation as ovulation precedes menstruation. This leaves women vulnerable to unplanned pregnancies. Community pharmacists (CPs) are frequently in contact with this patient group through the Supervised Consumption of OST service. This provides a timely opportunity to provide reproductive health (RH) advice. The aim of this study was to investigate pharmacists' views on providing a RH service to women receiving OST. Twenty semi-structured interviews based on the Capability-Opportunity-Motivation to Behaviour (COM-B) model and the Theoretical Domains Framework (TDF) were conducted between 2016 and 2017. Data analysis involved deductive coding using the TDF domains. The TDF domains were mapped onto the elements of the COM-B and used in the second step to create the framework and chart the data. The third step involved re-reading and clustering the codes, and inductive themes were generated to explain the data in depth. Nine of the 14 TDF domains, mapped into five elements of the COM-B, were identified. Five inductive themes were generated: 1) The pharmacists' experience and knowledge of reproductive health (RH) needs of women receiving OST, 2) The pharmacists' approach to providing advice, 3) The pharmacists' perception of the relationship with women receiving OST, 4) Social influences, and 5) Environmental factors. Community pharmacists feared causing offense to women receiving OST and described requiring cues as to when the service was needed. Pharmacists' highlighted a power imbalance in the relationship with women receiving OST. This could influence how receptive this patient group would be to pharmacy RH interventions. CPs' concerns of providing RH service could hinder a proactive service provision. Supporting good rapport and providing a structured consultation would increase the accessibility of such a service. •Reproductive health advice is triggered by social or physical cues from women.•Provision of this advice is subject to the reflective thinking of the provider.•A power imbalance characterizes supervised opioid substitution treatment.•Good rapport and a structured consultation were seen to increase the accessibility.